2017
DOI: 10.1080/08927014.2017.1374378
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of a novel antimicrobial peptide [W7]KR12-KAEK derived from KR-12 against Streptococcus mutans planktonic cells and biofilms

Abstract: The aims of this study were to describe the synthesis of a novel synthetic peptide based on the primary structure of the KR-12 peptide and to evaluate its antimicrobial and anti-biofilm activities against Streptococcus mutans. The antimicrobial effect of KR-12 and [W]KR12-KAEK was assessed by determining the minimum inhibitory (MIC) and minimum bactericidal (MBC) concentrations. The evaluation of anti-biofilm activity was assessed through total biomass quantification, colony forming unit counting and scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…mutans and S . sobrinus biofilm formation were examined using the microdilution method 41 . Briefly, overnight culture of S .…”
Section: Methodsmentioning
confidence: 99%
“…mutans and S . sobrinus biofilm formation were examined using the microdilution method 41 . Briefly, overnight culture of S .…”
Section: Methodsmentioning
confidence: 99%
“…Jannadi et al [89] synthesized Pep19-2.5 and Pep19-4LF and assessed that they inhibited S. mutans growth and biofilm formation. Similarly, Zhang et al [39] designed DPS-PI, Liang et al [90] designed LR-10, Da Silva et al [91] designed [W7]KR12-KAEK, and all of their antibacterial activities were evaluated by assessing the inhibition of S. mutans growth and biofilm biomass, furthermore assessing the destruction to biofilm morphology and the damage to the bacterial surface via scanning electron microscopy. In this current study, GERM CLEAN showed capabilities on reducing the initial adherence and disrupting the biofilm formation of S. mutans.…”
Section: Discussionmentioning
confidence: 99%
“…b–d). The differences in peptide length, hydrophobicity and net charges between the different Pug peptides may explain the different cytotoxicity of the Pug peptides (da Silva et al ).…”
Section: Resultsmentioning
confidence: 99%